Lipid Rafts and Alzheimer’s Disease: Protein-Lipid Interactions and Perturbation of Signaling - Hicks, David A.; Nalivaeva, Natalia N.; Turner, Anthony J. (Frontiers in Physiology, 2012)
Lipid rafts are membrane domains, more ordered than the bulk membrane and enriched in cholesterol and sphingolipids. They represent a platform for protein-lipid and protein-protein interactions and for cellular signalling events. In addition to their normal functions, including membrane trafficking, ligand binding (including viruses), axonal development and maintenance of synaptic integrity, rafts have also been implicated in the pathogenesis of several neurodegenerative diseases including Alzheimer’s disease (AD). Lipid rafts promote interaction of the amyloid precursor protein (APP) with the secretase (BACE-1) responsible for generation of the amyloid β peptide, Aβ. Rafts also regulate cholinergic signalling as well as acetylcholinesterase and Aβ interaction. In addition, such major lipid raft components as cholesterol and GM1 ganglioside have been directly implicated in pathogenesis of the disease. Perturbation of lipid raft integrity can also affect various signalling pathways leading to cellular death and AD. In this review, we discuss modulation of APP cleavage by lipid rafts and their components, while also looking at more recent findings on the role of lipid rafts in signalling events.